2016
DOI: 10.1080/2150704x.2016.1171925
|View full text |Cite
|
Sign up to set email alerts
|

Estimating potato leaf chlorophyll content using ratio vegetation indices

Abstract: Chlorophyll content at leaf level is an important variable because of its crucial role in photosynthesis and in understanding plant functioning. In this study, we tested the hypothesis that the ratio of a vegetation index (VI) for estimating canopy chlorophyll content (CCC) and one for estimating leaf area index (LAI) can be used to derive chlorophyll content at the leaf level. This hypothesis for estimating chlorophyll content at the leaf level was tested using simulations with the PROSAIL radiative transfer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 19 publications
(20 reference statements)
4
36
0
Order By: Relevance
“…Recent work by Kooistra and Clevers [9] has shown that other vegetation indices may be used to estimate leaf chlorophyll content (LCC). They found that the TCARI/OSAVI ratio and the CVI are the most promising as LCC estimators (Table 2).…”
Section: Field Radiometrymentioning
confidence: 99%
See 2 more Smart Citations
“…Recent work by Kooistra and Clevers [9] has shown that other vegetation indices may be used to estimate leaf chlorophyll content (LCC). They found that the TCARI/OSAVI ratio and the CVI are the most promising as LCC estimators (Table 2).…”
Section: Field Radiometrymentioning
confidence: 99%
“…Calibration curves between the WDVI and LAI were determined by performing both Cropscan measurements and LAI2000 Plant Canopy Analyser (LI-COR, Lincoln, NE, USA) measurements in the field at the same farm for potato experiments with similar set-ups in the years 2010-2014 [9]. Per plot, six measurements per potato row, for four rows (24 values per plot), were taken.…”
Section: Field Radiometrymentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is in agreement with expectations based on univariate correlations of traits over wavelengths (not shown). The red-edge slope is of particular relevance for leaf chlorophyll content (LCC) because of its enhanced sensitivity to varied and higher chlorophyll levels while circumventing saturation problems as observed in the blue and red due to vast chlorophyll-induced absorption (Gitelson, 2012;Kooistra and Clevers, 2016). Reliance on wavelengths at the onset of the near-infrared follows from the gradual stabilization of reflectance beyond the red-edge, which settles at higher values for increased chlorophyll levels (Lamb et al, 2002).…”
Section: Relevant Wavelengths For Plant Trait Predictionsmentioning
confidence: 99%
“…The ground-based apparent LAI (hereafter referred to LAI) was estimated based on weekly measurements with a Cropscan Multispectral Radiometer that used the weighted difference vegetation index (WDVI) [44] for estimating LAI. Calibration curves between the WDVI and LAI were determined by performing both Cropscan measurements and LAI2000 Plant Canopy Analyser measurements in the field at the same farm for potatoes grown in the years 2010-2014 [45]. In 2016, limited measurements with the LAI2000 were available, but validation with these measurements showed estimating LAI with Cropscan data was accurate.…”
Section: Study Areamentioning
confidence: 99%